Writing (a) Home in Times of Crisis: A Review of Scattered All Over the Earth (2018) by Yoko Tawada - Scarpulla, Evangeline (Satura, 2024)
In this dystopian novel, Tawada explores the concept of homeness in the twenty-first century by imagining future in which Japan has sunk into the sea as a result of the climate crisis. The only people left with intimate knowledge and memories of Japan are emigrants who resided outside the island nation when it disappeared. Among this small, exiled community is a young woman named Hiruko. The heartwarming story follows Hiruko as she embarks on a quest to seek out others who speak her native language. During her travels she meets and befriends a diverse cast of characters who each become invested in her search for the cultural remnants of her home country, while gaining a deeper understanding of their own sense of self and home along the way. Through this polyphonous novel, Tawada asks herself, her characters, and her readers questions like: what happens to a person when they lose their home? How does one create a home in a foreign and unfamiliar place? Is a home necessarily a physical space or can one find an intellectual and emotional home in the experience of community? By highlighting each character’s relationship with the concept of ‘home’, this review will provide an insight into the ways in which we navigate our desire to feel like a body at home, with the realities of the contemporary age – including migration, climate change, globalisation, and transnationalism. Thus, it will highlight how Tawada creatively engages with discourses on the evolving definitions and formulations of home and kinship, while reflecting on her personal experience as a migrant author who, for the time being, has left her native country and found new versions of home.